Recent Advances and Future Perspectives for Reinforcement of Poly(methyl methacrylate) Denture Base Materials: A Literature Review - Sahar Abdulrazzaq Naji; Tahereh sadat Jafarzadeh Kashi; Marjan Behroozibakhsh; Hamidreza Hajizamani; Sareh Habibzadeh (Shiraz University of Medical Sciences, 2018)
Poly(methyl methacrylate) (PMMA) is the most common material used to fabricate complete and partial dentures. Despite its desirable properties, it cannot fulfill all mechanical requirements of prosthesis. Flexural fatigue due to repeated masticatory and high-impact forces caused by dropping are the main causes of denture fractures. In the past, different reinforcing agents such as rubbers, macro fibers, and fillers have been employed to improve the mechanical properties of denture base resins. Development of Nano dentistry has introduced new approaches for reinforcement of dental materials. Interest in nanostructure materials is driven by their high surface area to volume ratio, which enhances interfacial interaction and specific new biological, physical, and chemical properties. Researchers to reinforce PMMA resins have used Nanoparticles (Nps) which were comprised of silver, Titania (TiO2), zirconia (ZrO2), alumina, and ceramic. Although different reports describe the use of nanofiber and nanotubes in dental composites, few studies have evaluated the reinforcement potential of nanofiber and nanotubes in PMMA denture base resins. The current article aims to review the different attempts to enhance the mechanical properties of denture base materials. We also focus on recent advances and potential future developments for reinforcement of the PMMA acrylic resins.